2018
DOI: 10.4018/978-1-5225-6114-9.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Compliance With IFRS Mandatory Disclosure Requirements

Abstract: This chapter examines Greek firms' compliance with IFRS mandatory disclosure requirements for the years 2006 and 2008. Using a checklist based on the IFRS disclosure requirements, a compliance score was calculated for each sample firm. Two methods of measuring compliance are used: the dichotomous method and the partial compliance method. By adopting both approaches proposed in literature for measuring compliance, the authors enhance the robustness of the findings of this study, while they provide empirical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Prior studies have not reached at a definite conclusion regarding the relationship between ownership structure and the level of disclosure. For example, Gao and Kling (2012) and Ballas et al (2018) concluded a positive relationship between the two variables, while Pichler et al (2018) concluded a negative relationship. To examine both stated variables of ownership, we formulated the following two hypotheses: H4a: There is a significant positive relationship between concentrated ownership and the extent of compliance with IFRS disclosure requirements in GCC member states.…”
Section: Ownership Structurementioning
confidence: 99%
“…Prior studies have not reached at a definite conclusion regarding the relationship between ownership structure and the level of disclosure. For example, Gao and Kling (2012) and Ballas et al (2018) concluded a positive relationship between the two variables, while Pichler et al (2018) concluded a negative relationship. To examine both stated variables of ownership, we formulated the following two hypotheses: H4a: There is a significant positive relationship between concentrated ownership and the extent of compliance with IFRS disclosure requirements in GCC member states.…”
Section: Ownership Structurementioning
confidence: 99%
“…The reason for the differences in the results regarding the impact of ownership structure on IFRS compliance across countries could be influenced by the differences in the legal origins [13]. For instance, Ballas et al, [28] found that closely-held firms show a higher IFRS compliance. Meanwhile, Rahman and Hamdan [78] in Malaysia found that the there is no significant association between outside blockholders' ownership and the level of IFRS compliance.…”
Section: Institutional Shareholdingmentioning
confidence: 99%
“…The empirical evidence show that audit type or audit firm with international affiliation positively influence compliance with IFRSs. For instance, Ballas et al, [28] in Greece found that there is a positive relationship between having international big auditing firm and IFRS compliance. Ebrahim [69] in Egypt examined compliance and enforcement of IFRSs as well as the effect of independent audit quality on IFRS compliance.…”
Section: Audit Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Literature regarding IFRS compliance showed mixed results (Agyei-Mensah, 2019;Alfraih & Almutawa, 2017;Allini, Ferri, Maffei, & Zampella, 2019;Al Mutawaa & Hewaidy, 2010;Al-Shammari, 2011;Ballas, Sykianakis, Tzovas, & Vassilakopoulos, 2018;Bova & Pereira, 2012;Demir & Bahadir, 2014;Ebrahim & Abdel Fattah, 2015;Fekete, Matis, & Lukács, 2008;Halbouni & Yasin, 2016;Hla et al, 2013;Tauringana & Chithambo, 2016;Tsalavoutas, 2011), which led many researchers to investigate these contradictory findings by conducting more studies in the area.…”
Section: Financial Reporting Quality: Compliancementioning
confidence: 99%